A Legacy of Animosity in the Southern Cone of South America? Attitudes of Paraguayan Consumers Towards Argentina and Brazil - Pisani, Michael; Cáceres Zarate, Alcides G.; Tello, José-Carlos; Becker, Silvio Eduardo (RAN - Revista Academia & Negocios, 2023)
Purpose: This article explores the interconnection between Paraguayan consumer behavior and products from Argentina and Brazil, situating the study within the context of past hostilities (animosity) and present uneven relations among the three nations. Methodology: Employing snowball sampling methodology, we conducted surveys with 385 middle- and upper-class Paraguayans from the greater Asunción area, both in-person and online, during the first half of 2022. The survey included questions on country-of-origin scales (specially consumer animosity), product preferences, and demographics. We developed and estimated a conceptual model connecting antecedents with Paraguayan consumer attitudes toward Argentina and Brazil using multiple regression. Findings: The impact of acculturation and the receipt of household remittances is significant on consumer animosity (CA). Elevated levels of acculturation intensify CA, while receiving household remittances acts as a mitigating factor against CA feelings. Practical Implications: Novel antecedents of consumer animosity inform and may guide decision-making for businesses and policymaking in addressing consumer animosity in Paraguay. Originality: This is the first study of consumer animosity in Paraguay.